IMPROVING THE FINANCIAL LITERACY OF STUDENTS BY USING TAX EXPERIMENTS IN THE EDUCATIONAL PROCESS - I. A. Maiburov; Yu. V. Leont’eva (Финансы: теория и практика, 2017)
The paper deals with the problem of development in students of financial literacy and tax competencies needed to ensure the functioning of developed civil society and determine the financial and tax discipline of future taxpayers. Due to the imminency of taxes and their importance for the financial stability of the state, the need to familiarize students with the basics of the country’s tax system, the importance of taxes for society, tax risks and the accountability of taxpayers for actions performed is justified. As a research method, a tax experiment is proposed: a survey of students’ behavior patterns in the tax payment sphere made before and after the getaware classes on the subject in question. The students were ranked by their risk appetite, and trends common to the behavior of future taxpayers were identified. The results of assessing the effectiveness of various types of educational technologies were discussed. The polls were conducted before and after classes among different student audiences. The effectiveness of the following training methods was evaluated: lectures, seminars, business games and field trips to the tax authorities. At lectures the teacher spoke about different taxes and the tax control. In practical classes students analyzed the components of different taxes. In business games, real tax payment or non-payment situations and possible sanctions for the violation were simulated. In field classes, students were involved in practice-oriented activities of tax bodies including a visit to the tax service museum, meeting with employees of tax bodies, participating as witnesses in investigative activities. Various training methods were ranked by their impact on the tax self-awareness of future taxpayers. It is concluded that active training methods are more effective because the willingness of students to pay taxes in full increases in such cases at a faster pace compared to passive methods.